(untitled) (Research, Society and Development, 2021)
Introduction: Pain is a frequent and unwanted symptom in cancer patients and may be a reflection of organic disease or antineoplastic treatments instituted. Occasionally, pharmacological therapy may have limitations in alleviating this condition, with the possibility of including non-pharmacological measures, such as complementary and integrative therapies in health. Objective: To evaluate the effectiveness of complementary and integrative therapies made available by the Unified Health System through the National Policy on Integrative and Complementary Practices in the relief of cancer related pain. Methodology: This is a systematic literature review, with studies published between 2016 and 2020, found in the PubMed database through descriptors validated by DeCS and inclusion and exclusion criteria. Results: Nine articles were selected, of which five researched and demonstrated the effectiveness of acupuncture in pain relief and reduction in the use of analgesics. One study listed the reduction of mucositis severity and pain intensity through the use of herbal plantago major L syrup. The article that studied reflexology demonstrated a reduction in pain intensity. Hypnosis and music therapy did not demonstrate effectiveness in relieving cancer pain among selected studies. Conclusion: Acupuncture is the most studied and most effective therapy for cancer pain relief. More technical-scientific support is needed for the inclusion and use of complementary and integrative practices with satisfactory safety and efficacy in cancer related pain relief.